2019
DOI: 10.1002/jcph.1433
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Clinical Impact of Formulation Variability: A Metoprolol Extended‐Release Case Study

Abstract: The objective of this research was to evaluate the impact of changes in the formulation of metoprolol extended‐release (ER) tablets on dissolution, pharmacokinetic, and exercise‐induced heart rate (EIHR) using a combined physiologically based absorption pharmacokinetic, and population pharmacokinetic/pharmacodynamic modeling and simulation approach. Using a previously developed physiologically based absorption pharmacokinetic model in DDDPlus and GastroPlus, we simulated the changes in drug release and exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Formulation changes were made through altering in vivo dissolution, which indicates that the platform can be subject to optimization by the operator. In another study, the simulated concentration-time profiles following formulation changes obtained by GastroPlus™ were used as pharmacokinetic input into NONMEM ® to determine if pharmacokinetics changes would affect the metoprolol pharmacodynamics significantly [62]. However, it was found that no significant therapeutic effect differences were produced despite pharmacokinetic changes, but this was attributed to the insensitivity of the endpoint used.…”
Section: Nonmem ®mentioning
confidence: 99%
“…Formulation changes were made through altering in vivo dissolution, which indicates that the platform can be subject to optimization by the operator. In another study, the simulated concentration-time profiles following formulation changes obtained by GastroPlus™ were used as pharmacokinetic input into NONMEM ® to determine if pharmacokinetics changes would affect the metoprolol pharmacodynamics significantly [62]. However, it was found that no significant therapeutic effect differences were produced despite pharmacokinetic changes, but this was attributed to the insensitivity of the endpoint used.…”
Section: Nonmem ®mentioning
confidence: 99%
“…The hypothesis generated by the pharmacoepidemiologic approach was then evaluated by integrated physiologically‐based absorption and population pharmacokinetic/pharmacodynamic models to evaluate the biological, physiological, and drug‐related and/or formulation‐related causes of the observed reduced efficacy or adverse event–drug pair report. Physiologically‐based absorption modeling coupled with population pharmacokinetic/pharmacodynamic modeling can be used to investigate if realistic changes in pharmaceutical variables (e.g., variables affecting dissolution rate, intestinal motility, or primary and secondary active transport across the intestinal membrane) may result in the observed purported reduced efficacy or adverse events arising from generic substitution . This strategy was applied retrospectively to a historic case example of extended‐release metoprolol as well as to antiepileptic drugs to establish the scientific approach ( Figure ) followed by a prospective application to direct acting oral anticoagulants to rank order the anticipated bleeding risk associated with soon‐to‐be marketed generic dabigatran, edoxaban, rivaroxaban, and apixaban.…”
Section: Challenges and Opportunities For The Futurementioning
confidence: 99%
“…Rather, perpetrators that are highly prevalent but perhaps with weaker drug–drug interaction profiles may be prioritized as they represent an overall larger absolute impact. Likewise, the extension of pharmacokinetic/pharmacodynamic and physiologically‐based pharmacokinetic models must consider the measurement of relevant population‐level clinical outcomes rather than more discrete pharmacological changes that are not captured in these databases, e.g., increased rate of heart attacks vs. increased heart rate variability . By using a combined approach, the strength of evidence is greatly increased and elevates its impact on regulatory and clinical decision‐making with much greater certainty.…”
Section: Challenges and Opportunities For The Futurementioning
confidence: 99%
See 1 more Smart Citation
“…To this end, we selected four representatives of DOACs: DABE, apixaban, rivaroxaban, and edoxaban to quantitively predict the impact of change in active pharmaceutical ingredient particle properties of these products on both BE and clinical outcomes using our previously demonstrated PBPK-population PK (Pop-PK)-pharmacodynamic (PD) approach. 18,19 Among the DOACs, DABE has a bioavailability of 3%-7%. It is consequently more likely to be affected by formulation design differences.…”
Section: Introductionmentioning
confidence: 99%